Aerodynamic Design of Megawatt Wind Turbine Blades with NPU-WA Airfoils. Issue 1 (April 2020) - Xu, Jianhua; Han, Zhonghua; Yan, Xiaochao; Song, Wenping
Abstract: The NPU-WA airfoils were designed at high design lift coefficient and high Reynolds number, with small sensitivity of the maximum lift coefficient to leading edge roughness and excellent geometric compatibility. Compared to the widely used airfoils, the NPU-WA airfoils have higher lift-to-drag ratio and higher maximum lift coefficient. This paper aims to design a megawatt wind turbine blade in order to demonstrate the advantage of the NPU-WA airfoils. The distributions of chord length and twist angle for a 2 MW wind turbine blade are optimized by a kriging surrogate model-based optimizer, with aerodynamic performance being evaluated by blade element-momentum theory. Results show that compared with the baseline blade, the maximum power coefficient of the optimized NPU blade is larger, and the chord lengths at all span-wise sections are smaller, which is benefit to structural weight reduction. It is shown that the NPU-WA airfoils feature excellent aerodynamic for the design of megawatt wind turbine blades.